ANALYSIS OF GENDER EQUALITY AND SOCIAL INCLUSION IN CLASS PARTICIPATION ENGLISH LEARNING TEN GRADE AT SMK NEGERI 1 TUHEMBERUA IN 2023/2024 - GULO, EFAIF MARTIN BERKATNIA; WARUWU, YAREDI; HAREFA, AFORE TAHIR; HAREFA, TRISMAN (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
This research examines gender equality and social inclusion in the participation of class X students during English learning at SMK Negeri 1 Tuhemberua for the 2024/2025 academic year. The primary goal of this research is to assess how gender roles and social dynamics in the classroom environment influence student participation and engagement. This research used a mixed methods approach, combining qualitative and quantitative data collection techniques, including classroom observations, surveys, and interviews with students.This analysis focuses on identifying participation patterns that may indicate gender bias or social exclusion. This analysis also explores barriers that prevent equal participation among students, such as cultural expectations, stereotypes, and differential treatment by educators. Additionally, this study evaluates the effectiveness of current pedagogical practices in fostering an inclusive learning environment that supports male and female students equally, regardless ofFindings from this research reveal a significant gap in participation rates between male and female students, with girls often facing greater barriers due to societal norms and expectations. This study also highlights the need for teachers to adopt more inclusive teaching strategies that actively promote gender equality and social inclusion. These findings underscore the importance of continued efforts to close the gender gap and create a more equitable educational experience for all students. It is hoped that the results of this research will inform the development of targeted interventions and policies aimed at improving gender equality. ABSTRAKPenelitian ini mengkaji kesetaraan gender dan inklusi sosial terhadap partisipasi siswa kelas X pada pembelajaran bahasa Inggris di SMK Negeri 1 Tuhemberua tahun ajaran 2024/2025. Tujuan utama penelitian ini adalah untuk menilai bagaimana peran gender dan dinamika sosial di lingkungan kelas mempengaruhi partisipasi dan keterlibatan siswa. Penelitian ini menggunakan pendekatan metode campuran, yang menggabungkan teknik pengumpulan data kualitatif dan kuantitatif, termasuk observasi kelas, survei, dan wawancara dengan siswa. Analisis ini berfokus pada mengidentifikasi pola partisipasi yang mungkin mengindikasikan bias gender atau eksklusi sosial. Analisis ini juga mengeksplorasi hambatan yang menghambat partisipasi setara di kalangan siswa, seperti ekspektasi budaya, stereotip, dan perlakuan berbeda dari pendidik. Selain itu, penelitian ini mengevaluasi efektivitas praktik pedagogi saat ini dalam menciptakan lingkungan pembelajaran inklusif yang mendukung siswa laki-laki dan perempuan secara setara, terlepas dari Temuan dari penelitian ini menunjukkan adanya kesenjangan yang signifikan dalam tingkat partisipasi antara siswa laki-laki dan perempuan, dimana anak perempuan seringkali menghadapi hambatan yang lebih besar karena dengan norma dan harapan masyarakat. Studi ini juga menyoroti perlunya guru untuk mengadopsi strategi pengajaran yang lebih inklusif yang secara aktif mempromosikan kesetaraan gender dan inklusi sosial. Temuan-temuan ini menggarisbawahi pentingnya upaya berkelanjutan untuk menutup kesenjangan gender dan menciptakan pengalaman pendidikan yang lebih adil bagi semua siswa. Hasil penelitian ini diharapkan dapat memberikan masukan bagi pengembangan intervensi dan kebijakan yang ditargetkan untuk meningkatkan kesetaraan gender.